Nghiên cứu thành phần hóa học cây xích thược (Paeonia veitchii Lynch. var Beresowskii - Kiệm và cộng sự, Phan Văn (Vietnam Journal of Chemistry, 2014)
From the methanolic extract of the roots of Paeonia veitchii Lynch. var beresowskii Shiff paeoniflorin (1), benzoylpaeoniflorin (2), gallic acid (3), gallic acid methyl ester (4), salicinol (5), isosalicin (6), benzoic acid (7), tianshic acid (8) were isolated by various chromatography methods. Their chemical structures were identified by NMR spectroscopic data. This is the first report of 5, 6 and 8 from family Ranunculaceae.